Answer:
63.6mm
Step-by-step explanation:
According to cosine rule;
AB² = BC²+AC²-2(BC)(AC)cos m<C
Substitute the given values
AB² = 70²+40²-2(70)(40)cos 64
AB² = 4900+1600-5600cos64
AB² = 6500-5600(0.4384)
AB² = 6500-2,454.87
AB² = 4,045.12
AB = √4,045.12
AB = 63.6mm
Hence the length of AB is 63.6mm
Answer:
3.25 minutes
Step-by-step explanation:
117 ÷ 36 = 117
Answer:
For a geometric sequence with recurrence of the form a(n)=ra(n-1) where r is constant, each term is r times the previous term. This implies that to get from the first term to the nth term, we need to multiply by n-1 factors of r.
Step-by-step explanation:
hii
you are looking so h*t and s**y..
Answer:
it will be 8 1/2
Step-by-step explanation:
Answer:
10. ( 7x + 2 ) × ( 5x + 1 )
Step-by-step explanation:
1. 35x² + 10x + 7x + 2
2. 5x × ( 7x + 2 ) + 7x + 2
3. ( 7x + 2 ) × ( 5x + 1 )